Automatic test case generation from UML state chart diagram: A survey - Salman, Yasir Dawood; Hashim, Nor Laily (Springer International Publishing, 2015)
The need for developing high-quality systems and applications with the minimum faults and error in them has been increased recently.In addition, a question of time and expenses that should be as low as possible always is concerned.Thus, it needs to be updated with the testing techniques that are more structured and automated which are used during the analysis and design phase.The significant role of automated testing techniques is that it helps speeding up the delivery of services of the products to the market with little chances of loss, and increases the software value. If the purpose were to decrease the expenses and getting closer to technology, then testing automation would be a crucial choice.The aim of this survey is to improve the understanding of UML diagram based testing techniques.Test case generation from state chart has been have focused on.Also, classify the various research approaches to their methods. The issues of test coverage associated with these methods have been discussed also.